Можливості та бар’єри для залучення позикових інвестиційних ресурсів підприємств на фінансовому ринку - Богуцька, О.А. (Стратегія і механізми регулювання промислового розвитку, 2017)
Проаналізовано стан і тенденції розвитку інвестиційної активності вітчизняних підприємств. Виявлено можливості забезпечення підприємств інвестиційними ресурсами на фінансовому ринку. Визначено основні інституціональні бар’єри, що стримують можливості підприємств у залученні інвестиційних ресурсів на ринках банківського кредитування та корпоративних облігацій. Надано рекомендації щодо підвищення ролі банківського кредиту та корпоративних облігацій у фінансовому забезпеченні інвестиційних проектів. Проанализированы состояние и тенденции развития инвестиционной активности отечественных предприятий. Выявлены возможности обеспечения предприятий инвестиционными ресурсами на финансовом рынке. Определены основные институциональные барьеры, сдерживающие возможности предприятий в привлечении инвестиционных ресурсов на рынках банковского кредитования и корпоративных облигаций. Представлены рекомендации по повышению роли банковского кредита и корпоративных облигаций в финансовом обеспечении инвестиционных проектов. According to the Strategy for Sustainable Development "Ukraine – 2020", economic growth in ecological and a non-exhaustive way is ensured by increased investments in high-tech production. One of the reasons for the low investment activity of enterprises in Ukraine is the limited possibility of using borrowed capital. The article is devoted to the possibilities of providing investment resources to enterprises in the financial market.
The purpose of the article is to give the reader some information about the main institutional barriers to attracting investment resources in the financial market of Ukraine. The article gives a detailed analysis of the sources for capital investments in Ukraine. Emphasis is placed on to bank loans and corporate bonds as sources of financing of capital investments.
The article considers the results of the analysis of financing for capital investments through a long-term bank loan. The review confirmed the low activity of banks in financing for capital investments. As a result of the analysis, the main reasons that banks constrain in lending to investment projects are identified. The author focuses on the short-term liability structure of commercial banks, the overstatement of the cost for credit resources and the high degree of non-performing loans. The necessity of using alternative borrowed sources for financing of capital investments is underlined. Such source is a corporate bond market. However, enterprises of Ukraine almost do not use such a method of attracting investments resources.
The author has identified the main institutional barriers to attracting credit resources in the market of corporate bonds and proposed directions for their minimization. Emphasis was also placed on the combination of the actions of formal and informal institutions at different levels – state, financial institutions, norms and rules, the system of dealings between economic entities. It is stressed that at the level of state institutions should be simplified the procedure for issuing and placing corporate bonds. At the level of financial institutions, a transparent system for assessing corporate bonds issues should be developed. The author stresses the need to create conditions for the priority direction of investment resources in the modernization of industry. To do this, it is necessary to develop tools for stimulating enterprises to borrow investment resources from the financial market.